Competition on the medical robotics markets for elderly - Leonid, Sobolev (IAES International Journal of Robotics and Automation (IJRA), 2023)
Population aging becomes one of the most significant 21st century social challenges. These challenges strongly reflect on the industry, labor, and financial markets. Population aging increases the demand for medicines, diagnostic equipment, and medical services. Both developed and developing countries have problems resulting from the current shortage of health workers and a limited supply of medical equipment. An alternative for medical staff growth is the robotization of medical services. However, robotics is economically justified when the costs of medical robots are lower than the construction of additional medical clinics and the increase in medical staff. Medical robotics appeared on the market later than the industrial and military ones but has recently found increasing use in high-income countries. Low and middle-income countries could not acquire expensive medical robots in sufficient quantities. The increased competition in the medical robotics market will lead to price reductions and make robotized services available for wide use. The article analyses the competition in segments of the medical robotics markets, connected with population aging.